Wearable device for prevention of postoperative and post‐discharge hypoxemia: A randomized pilot trial. Issue 4 (13th January 2023) - Li, Kai; Saab, Remie; Bravo, Mauro; Mascha, Edward J.; Han, Yanyan; Nault, Rod; Olson, Lloyd; Sessler, Daniel I.
Abstract: Background: The Oxalert Enhanced Pulse Oximeter (EPO) is a wearable device that detects and alerts patients to hypoxemia. In a preplanned pilot trial, we estimated the effect of continuous saturation monitoring with patient alerts on in‐hospital and post‐discharge saturation; we further assessed the feasibility of the intervention. Methods: Noncardiac surgical patients were randomized to either the Oxalert with patient alerts (Monitor + Alert, N  = 25) or the Oxalert without patient alerts (Monitor Only, N  = 24). Monitoring continued during hospitalization for up to 6 days and for 24 h after hospital discharge. Patients in each group were compared on time‐weighted average (TWA) SpO2 <90% (%) and area under SpO2 <90% (% * min) in‐hospital and after discharge using the Wilcoxon rank sum test, with the treatment effect median difference and 95% confidence interval (CI) estimated using the Hodges–Lehmann estimator of location shift. Results: We enrolled ≥2 patients per week, for a total of 49 patients in whom recording were obtained for a median [quartiles] of 91 [85, 95]% of the time in hospital. In‐hospital, TWA SpO2 <90% was a median [quartiles] of 0.11 [0.03, 0.25]% for Monitor + Alert and 0.29 [0.04, 0.71]% for Monitor‐Only patients, with estimated median difference (95% CI) of −0.1 (−0.4, 0)%, p  = .120. In hospital, the area under the curve (AUC) SpO2 <90% was a median [quartiles] of 635 [204, 1513] % * min for Monitor + Alert and 1260 [117, 5278] % * min for Monitor‐Only patients, with estimated median difference (95% CI) of −407 (−1816, 208) % * min, p  = .349. Post‐discharge, the estimated median difference (95% CI) was only −0.1 (−0.2, 0) %, p  = .307. Conclusions: The Oxalert system was well tolerated in both groups and enrollment was strong. Patients randomized to active Oxalert systems experienced half as many postoperative desaturation events while hospitalized, although the difference was not statistically significant in this small pilot trial. In contrast, the Oxalert system did not reduce post‐discharge desaturation. Detecting postoperative deterioation in surgical patients after they arrive on regular hospital wards, and even after they have been discharged home, can potentially facilitate necessary "rescue" interventions. Wearable devices assessing vital signs, including oxygenation, are a practical requirement. In this pilot study, a wearable pulse oximeter, with and without hypoxemia alarms, was tested for feasibility and acceptability for signal collection in postoperative cases, including at home. Results indicate that a full‐scale trial is warranted to test for possible clinical benefit with this type of "wearable" where late postoperative hypoxia could be a concern. The trial was registered at ClincialTrial.gov (NCT04453722).